Correction: Evaluating adherence to government recommendations for post-exposure rabies vaccine among animal-bite victims: A hospital-based study in Bangladesh. - Sadia Tamanna; Dilruba Yasmin; Sumon Ghosh; M Mujibur Rahaman; Amit Kumar Dey; Tushar Kumar Das; Sukanta Chowdhury (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0002506.].